Performing Indigeneity : Global Histories and Contemporary Experiences - Penny, H. Glenn; Graham, Laura R., 1956- (Book collections on Project MUSE., 2014)
"This engaging collection of essays discusses the complexities of "being" indigenous in public spaces. Laura R. Graham and H. Glenn Penny bring together a set of highly recognized junior and senior scholars, including indigenous scholars, from a variety of fields to provoke critical thinking about the many ways in which individuals and social groups construct and display unique identities around the world. The case studies in Performing Indigeneity underscore the social, historical, and immediate contextual factors at play when indigenous people make decisions about when, how, why, and who can "be" indigenous in public spaces. Performing Indigeneity invites readers to consider how groups and individuals think about performance and display and focuses attention on the ways that public spheres, both indigenous and nonindigenous ones, have received these performances. The essays demonstrate that performance and display are essential to the creation and persistence of indigeneity, while also presenting the conundrum that in many cases "indigeneity" excludes some of the voices or identities that the category purports to represent."--